Production performance of quails given chromium organic in ration - Sudrajat, Deden; Kardaya, Dede; Dihansih, E; Puteri, SFS (Indonesian Journal of Animal and Veterinary Sciences, 2014)
Egg production of quails depends on quality of ration. Nutrient manipulation by chromiun inclusion in ration is a possible way to improve production.  It is known that chromium mineral in form of GTF in blood has a role not only in enhancement of glucose entering cells through improvement of insulin activity but also in metabolism of lipid and synthesis of protein and elimination of heat stress to improve egg production. This study aimed at assessing egg production of quails fed ration containing chromium-yeast.  Sixty-four quails aged 40 days were used. A completely randomized design with 4 treatments and 4 replication was applied in this study. Treatment consisted of commercial ration + Cr 0 ppm (R1), commercial ration + Cr 0.5 ppm (R2), commercial ration + Cr 1 ppm (R3), and commercial ration+ Cr 1.5 ppm (R4). Measurements were taken on feed intake, egg weight, egg mass production, hen day, feed conversion rate, egg index, and egg shell thickness.  Results showed that A ration containing organic chromium as much as 1,5 ppm did not affect feed intake, egg production, egg weight, and eggshell thickness, however lowered feed conversion rate by up to 32.25% from that of control. Supplementation of  0,5 ppm chromium in the ration lowered the value of eggs index in the fourth week. Key Words: Quail, Egg Production, Chromium-Yeast